Influence of Corporate Governance Practices on Financial Success: Insights from Nepalese Commercial Banks - Subedi, Dhruba Prasad; Bhandari, Dilli Ram (Management Dynamics, 2023)
This study seeks to examine how board characteristics of corporate governance dimensions influence the financial health of commercial banks in Nepal. The descriptive and causal-comparative research design is employed to achieve the stated objectives. The population includes all 20 commercial banks licensed by NRB, from which 10 were selected as the sample. The analysis is based on longitudinal data collected from secondary sources over a ten-year period, from 2014 to 2023. Statistical techniques such as regression analysis and correlation are employed to analyze the data. The study reveals that after the enforcement of BAFIA in 2017, the obligatory requirements concerning board size, board independence, and board committees were strictly followed. Furthermore, the boardrooms during the study period exhibited a limited presence of women and independent directors. The results show that the size of the board and the presence of board committees have a statistically significant negative effect on ROE, while board independence has no significant impact on financial performance measures. However, board diversity shows a significant positive impact on the financial performance of commercial banks in Nepal. The results of this study hold practical significance for banking regulators, legislators, and financial institutions in formulating policies concerning board attributes.